Assessment of a diverse panel of transmitted/founder HIV-1 infectious molecular clones in a luciferase based CD8 T-cell mediated viral inhibition assay - Fernandez, Natalia; Hayes, Peter; Makinde, Julia; Hare, Jonathan; King, Deborah; Xu, Rui; Rehawi, Ola; Mezzell, Allison T.; Kato, Laban; Mugaba, Susan; Serwanga, Jennifer; Chemweno, James; et al. (Frontiers in Immunology, 2022)
Immunological protection against human immunodeficiency virus-1 (HIV-1) infection is likely to require both humoral and cell-mediated immune responses, the latter involving cytotoxic CD8 T-cells. Characterisation of CD8 T-cell mediated direct anti-viral activity would provide understanding of potential correlates of immune protection and identification of critical epitopes associated with HIV-1 control. The present report describes a functional viral inhibition assay (VIA) to assess CD8 T-cell-mediated inhibition of replication of a large and diverse panel of 45 HIV-1 infectious molecular clones (IMC) engineered with a Renilla reniformis luciferase reporter gene (LucR), referred to as IMC-LucR. HIV-1 IMC replication in CD4 T-cells and CD8 T-cell mediated inhibition was characterised in both ART naive subjects living with HIV-1 covering a broad human leukocyte antigen (HLA) distribution and compared with uninfected subjects. CD4 and CD8 T-cell lines were established from subjects vaccinated with a candidate HIV-1 vaccine and provided standard positive controls for both assay quality control and facilitating training and technology transfer. The assay was successfully established across 3 clinical research centres in Kenya, Uganda and the United Kingdom and shown to be reproducible. This IMC-LucR VIA enables characterisation of functional CD8 T-cell responses providing a tool for rational T-cell immunogen design of HIV-1 vaccine candidates and evaluation of vaccine-induced T-cell responses in HIV-1 clinical trials.